Sex hormones and sperm parameters after adjuvant oxaliplatin-based treatment for colorectal cancer - Philip Falk; Mira Severin; Åke Berglund; Marianne G. Guren; Eva Hofsli; Pia Österlund; Anne Tandberg; Jakob Eberhard; Halfdan Sorbye (Cancer Treatment and Research Communications, 2022)
Background: The incidence of colorectal cancer (CRC) in individuals of fertile age is increasing. Oxaliplatin is a cornerstone treatment in the adjuvant setting for stage III and high-risk stage II CRC. Limited data exist on possible side effects of oxaliplatin on fertility and gonadal function. More data is needed to guide possible fertility preservation procedures and aid evidence-based fertility counselling. Patients and methods: The aim of this study (EudraCT2006-002832-10) was to prospectively investigate sex hormones and sperm parameters after oxaliplatin-based adjuvant chemotherapy to clarify the risk of infertility and hypogonadism. Twenty males aged ≤55 years and 16 females aged ≤40 years were recruited from five hospitals in the Nordic countries. All had undergone radical surgery due to CRC and were given adjuvant oxaliplatin in combination with 5-fluorouracil. Measurement of luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone, sex hormone binding globulin (SHBG) and semen analysis were done in males, while LH, FSH and oestradiol were measured in females. Measurements were done prior to chemotherapy, after completion of adjuvant treatment and at follow-up 1 and up to 5 years after end of treatment. Results: FSH and testosterone levels increased in males after chemotherapy treatment but were restored at follow-up. No patients developed hypogonadism. There was a trend towards a decrease in sperm concentration during treatment (p = 0.063). When comparing sperm concentration and rapid progressive motility of sperms prior to chemotherapy and at follow-up, there were no differences, and no patients became permanently azoospermic by treatment. No distinct altering of gonadal function could be observed in females. Conclusions: Oxaliplatin in combination with 5-fluorouracil seems to induce transient decrease in sperm concentration with recovery and a minor transient increase in FSH in males. No distinct altering of gonadal function was observed in females. The risk of infertility and hypogonadism in males and females after adjuvant oxaliplatin-based chemotherapy seems low.